CRISPR/Cas9-Mediated Targeting of Susceptibility Factor eIF4E-Enhanced Resistance Against Potato Virus Y - Noureen, Azka; Khan, Muhammad Zuhaib; Amin, Imran; Zainab, Tayyaba; Mansoor, Shahid (Frontiers in Genetics, 2022)
Potato (Solanum tuberosum L.) is an important staple food around the world, and potato virus Y (PVY) is a major constraint for potato production. The VPg protein of PVY interacts with the translation initiation factor eIF4E of the host that works as a susceptibility factor during infection. The interaction between eIF4E and VPg was disrupted by CRISPR/Cas9. The homozygous conserved region of eIF4E of the potato variety “Kruda” was mutated by CRISPR/Cas9. Tracking of insertion, deletion, and conversion events was performed by Sanger sequencing with ∼15% editing efficiency. Truncated and mutated eIF4E proteins were unable to interact with VPg, and the virus was not able to exploit the host machinery for replication and systemic spreading. Mutated eIF4E lines showed enhanced resistance to PVYO strain. DAS-ELISA and RT-PCR were used for validation of the observed resistance. PVY resistance in tetraploid lines via CRISPR/Cas9 provides a route to develop novel resistant potato cultivars.